Polimorfismo XmnI e haplótipos do gene beta globina e suas relações com os níveis de hemoglobina Fetal em beta talassemia - Chinelato, Isabela Sandrin [UNESP] (2014)
The beta thalassemia are frequent genetic disorders and sufferers may have increased levels of hemoglobin A2 (Hb A2) and fetal hemoglobin (Hb F). The mutations present in individuals may be associated with different haplotypes of β–globin grouping. The objectives of this study consisted in investigating the frequencies of the XmnI polymorphism (-158 CT) and the pattern of the β-globin haplotypes in heterozygous and homozygous individuals for beta thalassemia, relate them to the levels of Hb F, and compare them with individuals without hemoglobinopathies. We analyzed 150 samples from heterozygous individuals with beta thalassemia, 22 homozygous and 150 individuals without hemoglobinopathies (control group). All samples were tested for classical hemoglobinopathies diagnosis and molecular analyzes Allele Specific PCR (AE-PCR) to confirm the mutation of beta thalassemia and PCR length polymorphism restriction fragment (PCR-RFLP) for identification of the polymorphism XmnI and sites of the β-globin haplotypes. Statistical tests were performed using STATISTICA 8.0 and Haploview 4.2 software. In beta thalassemia heterozygous individuals, mutation CD39 was the most common (62%) and in homozygous was the IVS-I-6 (22 %). We observed a significant difference in the levels of Hb F among the unidentified mutations and IVS-I-110 (p<0.05) in heterozygous individuals. The presence of the XmnI polymorphism was observed in all groups, but only heterozygous individuals for beta thalassemia was statistical difference in relation to increased levels of Hb F (p = 0.007). In the three groups were observed haplotype patterns I, II, IV, VI, VII and IX. For individuals heterozygous to beta thalassemia, the patterns II (24.3 %) and VII (32 %) were the most frequent, for individuals with beta thalassemia homozygous, the patterns I (29.5 %) and VII (38.6 %) and individuals without hemoglobinopathies, the patterns I (31%) and VII (28.3%). There was ...